Long-run trends or short-run fluctuations What establishes the correlation between oil and food prices? - Karoline Krätschell; Torsten Schmidt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper we use the frequency domain Granger causality test of Breitung/Candelon (2006) to analyse short and long-run causality between energy prices and prices of food commodities. We find that the oil price Granger causes all the considered food prices. However, when controlling for business cycle fluctuations this link exists especially at low frequencies. Thus, short-run phenomena like herd behaviour and speculation do not seem to have a considerable effect on the studied food prices. The relation between oil and food prices is rather established by long-term developments. A possible explanation for this could be the production of biofuel.
Keywords: C32; Q43; Q02; 330